Multiple roles of mitochondrial autophagy receptor FUNDC1 in mitochondrial events and kidney disease - Li, Kaiqing; Xia, Xue; Tong, Ying (Frontiers in Cell and Developmental Biology, 2024)
This article reviews the latest research progress on the role of mitochondrial autophagy receptor FUN14 domain containing 1 (FUNDC1) in mitochondrial events and kidney disease. FUNDC1 is a protein located in the outer membrane of mitochondria, which maintains the function and quality of mitochondria by regulating mitochondrial autophagy, that is, the selective degradation process of mitochondria. The structural characteristics of FUNDC1 enable it to respond to intracellular signal changes and regulate the activity of mitochondrial autophagy through phosphorylation and dephosphorylation. During phosphorylation, unc-51-like kinase 1 (ULK1) promotes the activation of mitophagy by phosphorylating Ser17 of FUNDC1. In contrast, Src and CK2 kinases inhibit the interaction between FUNDC1 and LC3 by phosphorylating Tyr18 and Ser13, thereby inhibiting mitophagy. During dephosphorylation, PGAM5 phosphatase enhances the interaction between FUNDC1 and LC3 by dephosphorylating Ser13, thereby activating mitophagy. BCL2L1 inhibits the activity of PGAM5 by interacting with PGAM5, thereby preventing the dephosphorylation of FUNDC1 and inhibiting mitophagy. FUNDC1 plays an important role in mitochondrial events, participating in mitochondrial fission, maintaining the homeostasis of iron and proteins in mitochondrial matrix, and mediating crosstalk between mitochondria, endoplasmic reticulum and lysosomes, which have important effects on cell energy metabolism and programmed death. In the aspect of kidney disease, the abnormal function of FUNDC1 is closely related to the occurrence and development of many diseases. In acute kidney injury (AKI), cardiorenal syndrome (CRS), diabetic nephropathy (DN), chronic kidney disease (CKD) ,renal fibrosis (RF) and renal anemia, FUNDC1-mediated imbalance of mitophagy may be one of the key factors in disease progression. Therefore, in-depth study of the regulatory mechanism and function of FUNDC1 is of great significance for understanding the pathogenesis of renal disease and developing new treatment strategies.